2021
DOI: 10.1128/jb.00646-20
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Identified Prophage Gene, ymfM , Causes SOS-Inducible Filamentation in Escherichia coli

Abstract: Rod-shaped bacteria such as Escherichia coli can regulate cell division in response to stress, leading to filamentation, a process where cell growth and DNA replication continues in the absence of division, resulting in elongated cells. The classic example of stress is DNA damage which results in the activation of the SOS response. While the inhibition of cell division during SOS has traditionally been attributed to SulA in E. coli, a previous report suggests that the e14 prophage may also encode an SOS-induci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The findings on similar MIC values of various groups E. coli in the present study were consistent with the lack of difference in the efflux pump related genes in the respective groups. A number of genes on cryptic prophages in E. coli have been reported to be involved in stress response including resistance to antibiotics such as novobiocin (37)(38)(39). None of these genes were overrepresented in LHR-positive isolates, despite the overrepresentation of cryptic prophage genes in general in this group.. Sublethal heat shock at 42C unfolds or misfolds cellular proteins, resulting in protein aggregates if these proteins are not refolded or degraded (40,41).…”
Section: Discussionmentioning
confidence: 90%
“…The findings on similar MIC values of various groups E. coli in the present study were consistent with the lack of difference in the efflux pump related genes in the respective groups. A number of genes on cryptic prophages in E. coli have been reported to be involved in stress response including resistance to antibiotics such as novobiocin (37)(38)(39). None of these genes were overrepresented in LHR-positive isolates, despite the overrepresentation of cryptic prophage genes in general in this group.. Sublethal heat shock at 42C unfolds or misfolds cellular proteins, resulting in protein aggregates if these proteins are not refolded or degraded (40,41).…”
Section: Discussionmentioning
confidence: 90%
“…Classically, during balanced growth, the population doubling rate (”) is directly related to the exponential rate of mass accumulation (λ = ln2*”) (Monod, 1949). When cells induce the SOS response, they become filamentous because they continue adding mass whilst delaying division as a result of the induction of SulA, YmfM and potentially other division inhibitors (Ansari et al , 2021). Heterogeneity in the level of SOS induction produces strong heterogeneity in the division rates of individual cells in the population.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few were found to have an association with inhibition of cell division and filamentation. 44,45 Ansari et al showed that overexpression of the SOS-induced ymf M gene caused filamentation and inhibition of Z ring formation, thereby halting cell division. 45 Filamentation helps E. coli to survive in different environments and contributes to antibiotic resistance.…”
Section: Lp-600 Induces Distinct Changes In the Transcriptome And Met...mentioning
confidence: 99%